Perception of Ayurveda Postgraduates to the Introduction of Formative Assessment - Vaishali Kuchewar; Shweta Parwe (Journal of Pharmacy and Bioallied Sciences)
Background: Assessment is a key feature of teaching and the curriculum. It has a massive impact on the quality of learning. It is observed that at the postgraduate level, 80% of trainees are not observed, and the remaining were observed not more than once in their three years programme. Current assessment of postgraduate students is at the end of three years. It predominantly assesses the cognitive part and no scope to improve their clinical skills. In view of it, this study was planned to conduct formative assessment for postgraduate students with the help of Mini-CEX and DOPS and to seek their perception. Methods: The postgraduate students of Department of Kayachikitsa and Panchakarma were invited voluntarily. Total 24 students (including first, second, and third year) were sensitized about the procedure of Mini-CEX and DOPS. The “encounters” were planned and schedule was displayed with names of student and teacher. The type of case was decided together by teacher and student. Each student was exposed to two Mini-CEX and two DOPS). Specific systemic examination and procedures were selected for Mini-CEX and DOPS, respectively. The time allocated for Mini-CEX and DOPS was as per the type of procedure but usually 15 minutes was allotted to each encounter for observation. Result: Overall students’ feedback about formative assessment was positive helping them to identify the gaps in their knowledge, and motivating them to learn. Conclusion: Mini-CEX and DOPS were well accepted by students as well as faculties as a formative assessment tool.